2015
DOI: 10.1007/s00705-015-2555-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 28B.rs12979860 genotype does not affect hepatitis C viral load in Egyptians with genotype 4 chronic infection

Abstract: Several host and viral factors affect the natural history of Hepatitis C Virus (HCV) infection. Interleukin 28B (IL28B).rs12979860 single nucleotide polymorphism (SNP) was found to predict viral clearance with and without therapy. Subjects with the CC (favorable) genotype of IL28B.rs12979860 were more likely to spontaneously clear the infection and respond favorably to therapy. These data suggest that subjects with the "favorable" CC genotype might have a lower viral load when compared to those with the "unfav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable example in this regard is IL-28B, whose polymorphisms have been reported to associate with ETR. However, the available IL-28B data is still somewhat conflicting 41 42 and to date, no universally applicable predictive marker of PEG-INF/RBV therapy has been established. Due to the significance of miR-122 in HCV infections, the association between hepatic miR-122 expression and ETR has been evaluated in some recent reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, Abdelwahab et al [27] demonstrated that SNP rs12979860 polymorphism does not affect viral load among CHC Egyptian patients.…”
Section: Interleukin-28b Polymorphism Is a Pharmacogenetic Predictor mentioning
confidence: 99%